The neurobiology of love and addiction: Central nervous system signaling and energy metabolism - Esch, Tobias; Stefano, George B (Cognitive, affective & behavioral neuroscience, 2025)
Despite our ongoing fascination with love's pleasures and pain, psychologists and neurobiologists have only recently begun to explore the neurobiological connections shared by feelings of romantic love and the experience of drug addiction. Functional imaging studies have revealed that feelings resulting from romantic love and those resulting from active drug use both activate the central reward system, which is a series of forebrain and midbrain structures that transmit signals primarily via dopamine release. Similarly, the relaxation response, which is a series of behaviors designed to alleviate stress-related physiologic sequelae, may also be helpful as an adjunct therapy for drug withdrawal. The benefits of the relaxation response and related mind-body practices may stem directly from its impact on mitochondria, organelles that are central to balanced energy production. Nitric oxide (NO) is a central neurotransmitter and also a key regulatory molecule that modulates mitochondrial respiration and oxygen utilization. Thus, we propose that observed behaviorally mediated changes that emerge from engaging the relaxation response may be the result of NO-mediated improvements in mitochondrial bioenergetics. Future research might focus on elucidating the important links between cellular bioenergetics, the relaxation response, and the central reward system and might explore NO modulation as a potentially effective target for drug development.
Keywords: Romantic love; Broken heart; Dopamine; Nitric oxide; Relaxation response; Stress; Brain; Drug addiction; Reward pathway; Bioenergetics